Comparative Performance Analysis of GRPC and Rest API Under Various Traffic Conditions and Data Sizes Using a Quantitative Approach - Ain, Moch. Zukhruf; Rizka Ardiansyah; Septiano Anggun Pratama; Muhammad Akbar; Nouval Trezandy Lapatta (Journal of Applied Informatics and Computing, 2025)
Web 3.0 presents challenges in efficient data exchange, especially in decentralized systems. REST API (HTTP/1.1) remains widely used due to its broad compatibility but has communication inefficiencies, while gRPC (HTTP/2) offers better performance with multiplexing and Protocol Buffers. This study compares REST API and gRPC under various traffic conditions and data sizes using Apache JMeter and Wireshark, measuring throughput, response time, latency, and data transfer efficiency. Results show that REST API has higher throughput in low-traffic scenarios (995 vs. 29.5 req/min) and faster GET response time (3 ms vs. 20 ms), while gRPC excels in large data transfers (276.34 KB/s vs. 134.1 KB/s) and stable latency (0.147 ms). However, ANOVA analysis (p > 0.05) indicates no statistically significant difference. REST API is ideal for standard web applications, while gRPC is suited for microservices and real-time systems.